Analysis of the Influence of Financial Ratio on Profit Growth of Banking Companies in the Banking Sector - Almardi, Silvanus; Aloysius Hari Kristianto; Jones Parlindungan Nadapdap (ProBisnis : Jurnal Manajemen, 2024)
This study aims to evaluate financial ratios on the implications for banking profit growth listed on the IDX for the period 2018-2022. In this study the ratios used are liquidity, solvency, profitability, bank finance, and market ratios to see the influence that occurs on banking profit growth. The data used in this study includes secondary data taken from the annual reports of banking companies listed on the IDX for the 2018-2022 period. The data collection technique used purpose sampling technique, so the sample used was 29 banking companies. The analysis technique used is multiple regression. The research on the variables of cash ratio, debt to asset ratio, return on equity ratio, non-performing loan, and price to earnings ratio results in that of the above variables partially only the variable return on assets has a positive and significant effect on the growth of banking profits listed on the IDX for the 2018-2022 period. While simultaneously the cash ratio variable, debt to asset ratio, return on equity, non-performing loan, and price to earnings ratio have a significant effect on the profit growth of banking companies listed on the IDX for the 2018-2022 period.